Determination of albumin, glucose, and creatinine employing a single sequential injection lab-at-valve with mono-segmented flow system enabling in-line dilution, in-line single-standard calibration, and in-line standard addition - Kanokwan Kiwfo (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/). A mono-segmented sequential injection lab-at-valve (SI-LAV) system for the determination of albumin, glucose, and creatinine, three key biomarkers in diabetes screening and diagnosis, was developed as a single system for multi-analyte analysis. The mono-segmentation technique was employed for in-line dilution, in-line single-standard calibration, and in-line standard addition. This made adjustments to the sample preparation step easy unlike the batch-wise method. The results showed that the system could be used for both fast reaction (albumin) and slow reaction (glucose with enzymatic reaction and creatinine). In the case of slow reaction, the analysis time could be shortened by using the reaction rate obtained with the SI-LAV system. This proposed system is for cost-effective and downscaling analysis, which would be applicable for small hospitals and clinics in remote places with a small number of samples but relatively fast screening would be needed.